Egypt Disaggregated Social Accounting Matrix, 2010/11 - International Food Policy Research Institute; Central Agency for Public Mobilization and Statistics, Arab Republic of Egypt (International Food Policy Research Institute, 2016)
This data study includes disaggregated social accounting matrix (SAM) for the Egyptian economy for year 2010/11. This new SAM builds on the previous SAM 2010/11 built and published by Central Agency for Public Mobilization and Statistics (CAPMAS) with the support of the International Food Policy Research Institute (IFPRI). This SAM was constructed with a special focus on the agriculture sector and on income distribution amongst households. It is composed of 52 activity sectors, 49 commodity sectors, three types of factors of production: labor (unskilled labor, semiskilled labor, and skilled labor), land, and capital; a government account, as well as, enterprises, households, savings and investment, and the rest of the world (ROW). The household sector is divided spatially into urban and rural households, with each disaggregated into 10 deciles according to expenditure. The disaggregated SAM allows for analyzing agricultural issues at the detailed crop level and to better understand the potential impacts of policy changes for both better off and more vulnerable households.